(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
In geological structure of Bardzravan ore field the main role belongs to the volcanic-sedimentary formations of the lower and middle Eocene. These rocks are covered unconformably with lava and pyroclastic formations of salvard suit of the middle-upper Miocene. Metasomatic rocks, which confined to the gold-bearing, are widely distributed within the ore field. The article also presents the data of geophysical studies, which were made in the central part of the ore field.